Optical coherence tomography evaluation of choroidal structure changes in diabetic retinopathy patients: A systematic review and meta-analysis - Jiang, Jikuan; Liu, Jingyuan; Yang, Jia; Jiang, Bing (Frontiers in Medicine, 2022)
Introduction: Diabetic retinopathy (DR) is one of the major causes of blindness among working-aged adults worldwide. This study aimed to evaluate the differences in the subfoveal choroidal thickness (SFCT) and choroidal vascularity index (CVI) using optical coherence tomography (OCT) of patients with diabetic eyes with no retinopathy (NDR) and with diabetic retinopathy (DR). Methods: We performed a comprehensive literature search of the PubMed, Embase, and Cochrane Library databases up to October 2021. The weighted mean difference (WMD) with the 95% confidence interval (CI) was pooled for continuous outcomes. Results: Twenty-three cross-sectional studies comprising 2534 eyes including 1070 NDR eyes, 1464 DR eyes were included in the systematic review and meta-analysis. The pooled results showed SFCT was significantly thicker in DR than in NDR patients after adjusting for axial length (WMD=27.90 μm; 95% CI: 11.51 to 44.28; P=0.001), and the CVI was significantly lower in DR patients (WMD=-1.59; 95% CI: -2.67 to -0.52; P=0.004). Conclusion: We described changes in the SFCT and CVI in DR. Resultantly, the CVI and SFCT may be valuable parameters for monitoring the onset of DR and helpful for a better understanding of the role of the choroid in the pathological process of DR.